Gender Based Verbal Abuse among Civil Servants in Edo State, Nigeria - Obasohan, I. Oguns - (NIU Journal of Humanities; Vol. 10 Núm. 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
This study examined the perception of gender-based emotional violence among civil servants in Edo state. The study also tested the hypothesis on the influence of demographic attributes on employees’ perception of gender-based emotional violence in Edo State civil service. The study adopted the survey research design and employed a structured questionnaire to elicit information from respondents. The responses from the questionnaire copies were analyzed using descriptive statistics such as frequency distribution, mean and standard deviation. Chi-Square (χ 2 ) was used as an inferential statistical technique for testing the research hypotheses at a 5% level of significance. All of the statistical analyses in this study were carried out using the Statistical Package for the Social Sciences (SPSS version 24). 58.4% of the respondents investigated affirmed the occurrence of verbal abuse in Edo State civil service mainly perpetrated by supervisor/immediate boss, client/customers, and colleagues/co-workers. The study also showed that low performance and productivity, mental health issues, rage, anxiety, and sadness, as well as a decline in job satisfaction, are all effects of gender-based verbal abuse among Edo State public servants. The study recommends that the Edo State Government should set up specialized courts to handle gender-based violence-related cases swiftly. Keywords: Gender-Based Violence, Verbal Abuse, Work Performance